PRODUKSI DAN KECERNAAN IN-VITRO RUMPUT GAJAH PADA BERBAGAI IMBANGAN PUPUK NITROGEN DAN SULFUR - Sri Susanti (BUANA SAINS, 2007)
The research was aimed to observe production and in-vitro digestibility of Elephant grass with different ratio N : S fertilizer. This research with experimental methods was executed in two phases. The first phase was Elephant grass cultivation with different ratio of N : S fertilizer. The second phase was measurement of in-vitro digestibility. Seven treatments and three blocks were arranged in a Randomized Block Design. The results showed that fertilization of S did not significantly affect production and digestibility of Elephant grass. Over application S fertilizer reduced in-vitro digestibility (dry matter / DM and organic matter / OM). The best of DM digestibility (62,59%) and OM digestibility (65,41%) were at ratio N : S fertililzer = 300 : 0